Rhetorical structures in academic research writing by non-native writers - Ab Rahim, Ina Suryani; Abd Aziz, Noor Hashima; Yaacob, Aizan; Abd Rashid, Salleh; Desa, Hazry (Sciedu Press, 2013)
Writers of research articles are expected to present research information in a structured manner by following a certain rhetorical patterns determined by the discourse community.Failures to keep to the writing standard and rhetorical pattern are likely to lower the acceptance rate. While producing a research article is understandably a complex task, it is even more difficult if one is writing in his or her second or third language. Even if grammatical mistakes can be ironed out by a language editor, researchers are on their own when it comes to rhetorical presentation of their research ideas. The available research writing guidelines constructed in the native speaker context often fall short in addressing rhetorical aspects related to cultural issues that have been known to influence most non native English (NNE) writings. Motivated by the complexity of rhetorical presentation in research articles and the problems on writing research articles by NNE writers, this paper is aimed to explore the rhetorical moves used by the Malaysian writers in the introduction section of Computer Science research articles for journal publication.CARS model (Swales, 2004) is used to analyze the rhetorical moves in the introduction section of Computer Science research articles by the Malaysian writers.The study begins with a corpus compilation of five research articles (RA) by the writers followed by move analysis use in the CARS model (Swales, 2004) was conducted to analyze the articles.The analysis revealed that majority of the writers adopted most of the rhetorical strategies in Swales model (2004).The paper concludes that CARS model is suitable in identifying the rhetorical moves in the RA by Malaysian writers.